A systematic review of interventions to increase physical activity and reduce sedentary behaviour following bariatric surgery. (June 2022) - James, Jennifer D.; Hardeman, Wendy; Goodall, Mark; Eborall, Helen; Sprung, Victoria S.; Bonnett, Laura J.; Wilding, John P.H.
Abstract: Background: Bariatric surgery promotes weight loss and improves co-morbid conditions, with patients who are more physically active having better outcomes. However, levels of physical activity and sedentary behaviour often remain unchanged following surgery. Objectives: To identify interventions and components thereof that are able to facilitate changes in physical activity and sedentary behaviour. Eligibility: Physical activity and/or sedentary behaviour must have been measured, pre and post intervention, in patients who have undergone bariatric surgery. Study appraisal and synthesis methods: : Four databases were searched with key-words. Two researchers conducted paper screening, data extraction and risk-of-bias assessment. Results: Twelve studies were included; eleven were randomised. Two were delivered presurgery and ten postsurgery; five found positive effect. Moderate to vigorous physical activity increased in three studies, two of which also found a significant increase in step count. The fourth found a significant increase in strenuous activity and the fifth a significant increase in metabolic equivalent of task/day and reduced time spent watching television. Limitations: Meta-analysis could not be conducted due to heterogeneity of outcomes and the tools used. Conclusion and implications of key findings: This review has identified interventions and components thereof that were able to provoke positive effect. However, intervention and control conditions were not always well described particularly in terms of behaviour change techniques and the rationale for their use. Systematic review registration number: PROSPERO (CRD42019121372)